Aplikasi Pendeteksi Jauh Dekat Posisi Suatu Objek Dengan Menggunakan Kinect For Windows - Jeffrey Harto Muntjang Disurja; Liliana Liliana; Gregorius Satiabudhi (Jurnal Infra, 2016)
The growth of technology are used on every aspect of human lifes. One that rapidly growing is technology on video games. Virtual reality is on that raise the intereset of game developer to improve the quality of gameplay. By using virtual reality, user can interact directly with the game world this will give the user feeling of reality. One of the technology that used in virtual reality is kinect. On that aspect this research about the depth sensor of kinect device is chosen. Depth sensor will be used to get an input of user motion to make a different result based on the depth movement. This research is meant to create an application that can give a different output on virtual reality game based on depth input that kinect catch from user motion.Kinect is used as the game controller in the result of this virtual reality game research. Kinect device will used to control the game character, user only need to move their body parts tomove the character this kind of controller will led to a feeling of reality experienced by user. Therefore to increase that feel, the depth movement that user do will be calculated using physics to give a more better output.The test result shown that kinect device can give good output by using the depth sensor. The test can divide the speed that kinect catch can be classified to 4 stage dan each of this stage can giive a different reaction on the game.